Modelling the feed mix for poultry production, the case of Adama Musa farms, in Ghana - Amponsah, S. K.; Otoo, Dominic; Peprah, A. K.; Ampofo, S. D. (International Journal of Applied Mathematical Research, 2015)
The poultry industry has a significant importance on national economy. It is a popular industry for the small holders with tremendous contribution to Gross Domestic Product (GDP) and employment creation. Poultry feed cost represents over sixty (60) percent of the total cost of poultry production; consequently, efficient feed formulation practice is required for a sustainable poultry industry. Many Ghanaian poultry farmers, however, employ inefficient methods like rule of thumb, experiences, and intuition to handle feed formulation problem. This paper presents a deterministic linear programming model to solve blending problem facing poultry farmers, using locally available feed ingredients from the Ghanaian poultry industry. In the model, we shall minimize cost of producing a particular diet and maintain the ingredient. Over 3% reductions in the cost of producing broiler starter and finisher feed formulation compared to the existing method on the farm was achieved.